(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
Transplants are a set of surgical techniques characterized by replacing damaged organs with new and healthy ones. There are historical references, from the earliest times of humanity where organ replacements, viscera or parts of the body are collected and even the combination of body parts of different animal species that recall the therapeutic substitution of the transplant. There are references in mythology, at the level of legends, in the description of miraculous facts, although there are more scientific data concerning various attempts of this type of substitutions. There are specific contributions on transplants, attempts made in animal experiments and, on the other hand, historical milestones that have made it possible for this type of technique to be considered routine in routine surgical practice. A historical journey is made in the work, analyzing these contributions.